2022
DOI: 10.1186/s13287-022-03049-x
|View full text |Cite
|
Sign up to set email alerts
|

ADSCs-derived exosomes ameliorate hepatic fibrosis by suppressing stellate cell activation and remodeling hepatocellular glutamine synthetase-mediated glutamine and ammonia homeostasis

Abstract: Background Hepatic fibrosis is a common pathologic stage in chronic liver disease development, which might ultimately lead to liver cirrhosis. Accumulating evidence suggests that adipose-derived stromal cells (ADSCs)-based therapies show excellent therapeutic potential in liver injury disease owing to its superior properties, including tissue repair ability and immunomodulation effect. However, cell-based therapy still limits to several problems, such as engraftment efficiency and immunoreactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The broken balance between extracellular matrix (ECM) degradation and deposition promoted the initiation of liver fibrosis [ 55 , 56 ]. It has been proven that hADSCs contribute to preventing or even eliminating further liver fibrogenesis by downregulating the expressions of inflammatory genes and inhibiting the activation of HSCs [ 18 20 , 57 , 58 ]. Consistently, our present data reveal that hADSC infusion ameliorated the pathological presentation of BDL-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broken balance between extracellular matrix (ECM) degradation and deposition promoted the initiation of liver fibrosis [ 55 , 56 ]. It has been proven that hADSCs contribute to preventing or even eliminating further liver fibrogenesis by downregulating the expressions of inflammatory genes and inhibiting the activation of HSCs [ 18 20 , 57 , 58 ]. Consistently, our present data reveal that hADSC infusion ameliorated the pathological presentation of BDL-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of their immunomodulatory capacities, endogenous tissue repair potential, and other unique properties, ADSCs have been extensively utilized for the treatment of diverse diseases [ 14 17 ]. Previous studies have shown that ADSC transplantation could constitute an alternative therapeutic approach to combating or ameliorating hepatic disease owing to their positive effects on the modulation of inflammation and the alleviation of fibrosis formation [ 18 20 ]. Unfortunately, the survival crisis that mesenchymal stem cells (MSCs) inevitably suffer upon being transplanted into the host remains a major obstacle to translational success [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and Identification of ADSC-Derived Exosomes: ADSC-exos were isolated from cell supernatants as described previously [56,57] When ADSCs reached 80−90% confluence, the FBS-free culture medium was changed. The culture supernatant at 3000 X g was centrifuged for 30 min to remove dead cells, followed by centrifugation at 10 000 X g for 30 min to eliminate cellular debris.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, ADSC-EXO may reverse the pro-fibrotic phenotype in vivo and in vitro . Upon more in-depth study, they concluded that ADSC-EXO improve LF by inhibiting HSC activation and remodeling hepatocyte glutamine synthetase-mediated glutamine and ammonia homeostasis ( 80 ). In addition, umbilical cord plasma-derived exosomes (UCB-EXO) may be a promising therapy for LF.…”
Section: Clinical Application Of Exosomes In Lfmentioning
confidence: 99%